Contact Transfer Printing of Side Edge Prefunctionalized Nanoplasmonic Arrays for Flexible microRNA Biosensor. Issue 9 (24th June 2015) - Lee, Jihye; Park, Jiyun; Lee, Jun‐Young; Yeo, Jong‐Souk
<x xml:space="preserve">Abstract</x> For a nanoplasmonic approach of wearable biochip platform, understanding correlation between near‐field enhancement on nanostructures and sensing capability is a crucial step to improve the sensitivity in biosensing. A novel and effective method is demonstrated to increase sensitivity with the enhanced electric fields and to reduce noise with targeted functionalization enabled by transferring side edge prefunctionalized (SEPF) nanostructure arrays onto flexible substrates. Nanostructure sidewalls have selective biochemically functional terminals for the hybridization of microRNAs (miRNAs) and the immobilization of resonant nanoparticles, thus forming hetero assemblies of the nanostructure and the nanoparticles. The unique configuration has shown ultrasensitive biosensing of miRNA‐21 in a 10 × 10−15m level by a red‐shift in scattering spectra induced by a plasmon coupling. This ultrasensitive SEPF nanostructure arrays are fabricated on a flexible substrate using a contact transfer printing with a release layer of trichloro(1H, 1H, 2H, 2H‐perfluorooctyl)silane. The introduction of the release layer at a prefunctionalizing step has proven to provide selective functionalization only on the sidewalls of the nanostructures. This reduces a background noise caused by the scattering from nonspecifically bound nanoparticles on the substrate, thus enabling reliable and precise detection.